Rockburst mechanism of rock mass with structural planes in underground chamber excavation. (September 2022) - Wu, J.; Zhang, X.Y.; Yu, L.Y.; Zhang, L.W.; Wu, T.
Highlights: Similar materials suitable for the rockburst model test are configured by orthogonal proportioning tests and physical mechanics tests. The rockburst mechanism of rock mass with structural planes in underground chamber excavation is studied by model test and numerical simulation. The failure modes and laws of surrounding rock mass with different structural planes during chamber excavation are obtained. Abstract: Natural rock mass generally contains discontinuous structural planes, such as joints, fractures and faults, which have great influence on the occurrence of rockburst. The rockburst mechanism of rock mass with structural planes in underground chamber excavation is studied by means of model test and numerical simulation in this paper. Firstly, quartz sand, barite powder, gypsum powder, cement and water are selected as raw materials to configure the similar materials suitable for the rockburst model test. Secondly, four working conditions of none structural plane, single structural plane, multiple structural planes and through structural plane are designed, and the corresponding rockburst model tests are carried out. The stress and displacement laws of surrounding rock during excavation are analyzed. Finally, the numerical calculation of chamber excavation is conducted under the above four working conditions and the model test is verified. The failure modes and laws of surrounding rock mass with different structural planes during chamber excavation are obtained. The results show that: (i) After the tunnel excavation in rock mass with single structural plane, the tension of structural plane and the expansion of fractures occur, accompanied by small-scale rockburst. (ii) After the tunnel excavation in rock mass with multiple structural planes, the stress level of surrounding rock mass decreases significantly and no rockburst occurs, but the surrounding rock is prone to large-scale collapse or spalling. (iii) After the tunnel excavation in rock mass with through structural plane, the fractures appear in the vault and arch bottom and expand rapidly, accompanied by rockburst phenomena such as granules ejection. The research results of this paper are of great significance for understanding the deformation and failure mechanism of rock mass with structural planes in the underground chamber excavation.